Constraint on foreland basin migration in the Zagros mountain belt using Sr isotope stratigraphy. (30th January 2015) - Pirouz, Mortaza; Simpson, Guy; Chiaradia, Massimo
Abstract: We have constrained the time‐space migration of the Zagros foredeep basin by performing Sr isotope stratigraphy on 31 samples of marine macrofossils from Neogene sediments now exposed in the Zagros mountain belt in southwest Iran. Our results show that these deposits (represented mainly by the Mishan Formation) are strongly diachronous, with ages ranging between 17.2 ± 0.2 and 1.1 ± 0.1 Ma. These deposits are older in the west (Dezful region) and become progressively younger towards the south and the south‐east (Fars region). Our results show that the marine foredeep was replaced by a fluvial sedimentary environment between ca . 14 and 12 Ma in the western sector, while this occurred between ca . 8 and 1 Ma in the eastern sector, becoming younger towards the south. These results enable us to show that the foreland basin migrated perpendicular to the orogen at rates of between 17.5 and 50 mm year −1 throughout the Neogene, exceeding migration rates in the Alps, Pyrenees, Apennines and Himalayan foreland basins. The sporadically elevated rates in the Zagros appear to be related to times when major widely spaced pre‐existing basement faults became reactivated. Finally, our results, when combined with published data, have enabled us to establish a new chronostratigraphic diagram for the Neogene portion of the Zagros foreland basin. Our study highlights that foreland basins are extremely dynamic settings where depocentres and palaeoenvironments may change rapidly in both time and space in relation to migrating deformation.